Space Design in Batur Sari Villa in Sanur, Bali - Putra, Ida Bagus Gede Kresnayana; Wiryawan, I Wayan (Journal of A Sustainable Global South; Vol 1 No 2 (2017): August 2017DO - 10.24843/jsgs.2017.v01.i02.p06, 2017)
Villa is a temporary place, which is located in a distant from crowded area in general villas are built in a place with not many residents and surrounded by beautiful nature to give comfort and serenity. One of the demands is how to maximiz-ing environmental atmosphere into design. Batur Sari villa is located in Sanur, which is identic with the coast. The de-mands is how to create the beach atmosphere in a villa and put into a design. An interior design with nautical concept could be a solution. The aims of interior design is for the development the function and psychological space and with this concept it can gives an environmental atmosphere inside the villa. Nautical concept identic with holyday feels in the beach. Sunshine, waves and sands could become inspirations, with the application of the concept inside the villa, a villa design could fulfill the needs of relax and serenity atmosphere with sorroundings characteristics that’s is needed. Index Terms — villa, interior design, nautical concept